TRANSPLANTOLOGY : A REQUIREMENT OF THE TIME OR THE NEXT EVOLUTIONARY STEP OF HIGH-TECH SURGERY? - Akbarov, MM.; Ismailov , S.I.; Nazirov , F.G.; Ibadov , R.A.; Bahritdinov , F.Sh.; Dzhanbekov , T.A.; Nishanov , M.Sh.; Omonov , O.A.; Hayaliev, R.Ya.; Shayusupov, A.R.; Matkarimov, Z.T.; Sabirov, J.G.; et al. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
This article presents a brief outline of the history of transplantation service in the Republic of Uzbekistan, which originated in the kidney transplantation Center Academy of Sciences of Uzbekistan. In article highlighted the role of outstanding scientists of Uzbekistan, their works and efforts aimed on creating a separate direction of clinical and scientific medicine. In article presents the achievements of the scientific school of U.A. Aripov and V.V. Vakhidov academicians of the Academy of Sciences of the Republic of Uzbekistan. It reflects the ups and downs of the national service of transplantation nephrology, as well as the birth of the national school of kidney and liver transplantation, held in the State Institution "Republican Specialized Scientific and Practical Medical Center of Surgery (RSSPMCS) named after Academician V. Vakhidov" led by Academician F.G. Nazirov and gave the "second breath" of the national transplant school. Special attention was paid to the current problems of domestic transplantology, there were reflected the moral, ethical and regulatory issues that accompany this scientific and clinical direction, the latest research conducted in the world in this way was indicated. Article presented results of kidney and liver transplantation in Uzbekistan and outlined prospects for further scientific and clinical directions.